Implementasi Kebijakan E-KTP Dalam Pelayanan Administrasi Kependudukan Kota Padangsidimpuan - Erlinda Habib Hasibuan; Badaruddin Badaruddin; Karyono Karyono (Universitas Medan Area, 2020)
This study aims to determine the implementation of the Electronic Identity Card (e-KTP) policy in the Population and Civil Registry Office of Padangsidimpuan City. In this study using the George C Edward III implementation model that is considered very appropriate and has detailed variables. This study uses a qualitative approach to data collection techniques through observation, interviews, and documentation. Data analysis techniques using data reduction, data presentation, and drawing conclusions. The results of this study indicate, the implementation of the Electronic Identity Card (e-KTP) policy has been running since 2015. However, there are still some problems encountered. Of the 4 variables in the George C Edward III implementation model namely communication, resources, disposition and bureaucrat structure. The results showed that the Disduk Capil Kota Padang Sidempuan only fulfilled 2 variables. The 2 variables are fulfilled namely disposition and bureaucrat structure. While two more variables that are not fulfilled are communication and resources.